2012
DOI: 10.1186/1742-2094-9-62
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline corrects early, pre-plaque neuroinflammation and inhibits BACE-1 in a transgenic model of Alzheimer's disease-like amyloid pathology

Abstract: BackgroundA growing body of evidence indicates that inflammation is one of the earliest neuropathological events in Alzheimer's disease. Accordingly, we have recently shown the occurrence of an early, pro-inflammatory reaction in the hippocampus of young, three-month-old transgenic McGill-Thy1-APP mice in the absence of amyloid plaques but associated with intracellular accumulation of amyloid beta petide oligomers. The role of such a pro-inflammatory process in the progression of the pathology remained to be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 103 publications
2
66
0
1
Order By: Relevance
“…; 45 mg/kg/day for three weeks) to an Aβ 1- 4 2 -infused rat model and Tg2576 mice (knock in of human APPsw driven by the hamster prion protein promoter; 10 mg/kg/day minocycline, 5 days a week for 9 months) [112]. Importantly, minocycline (50 mg/kg/day) lowered brain inflammatory markers (COX-2, iNOS, and IL-1β), APP expression, and BACE1 activity when administered intraperitoneally for one month to young, pre-plaque McGill-Thy1-APP mice (knock in of human APPsw/ind driven by the murine Thy1.2 promoter) [113]. However, in the latter study the authors reported liver and peritoneal toxicity, which “precluded the completion of behavioral testing for learning and memory” [113].…”
Section: Evidence That Tnf-α Modulation May Slow or Prevent Alzheimentioning
confidence: 99%
See 1 more Smart Citation
“…; 45 mg/kg/day for three weeks) to an Aβ 1- 4 2 -infused rat model and Tg2576 mice (knock in of human APPsw driven by the hamster prion protein promoter; 10 mg/kg/day minocycline, 5 days a week for 9 months) [112]. Importantly, minocycline (50 mg/kg/day) lowered brain inflammatory markers (COX-2, iNOS, and IL-1β), APP expression, and BACE1 activity when administered intraperitoneally for one month to young, pre-plaque McGill-Thy1-APP mice (knock in of human APPsw/ind driven by the murine Thy1.2 promoter) [113]. However, in the latter study the authors reported liver and peritoneal toxicity, which “precluded the completion of behavioral testing for learning and memory” [113].…”
Section: Evidence That Tnf-α Modulation May Slow or Prevent Alzheimentioning
confidence: 99%
“…Consequently, most anti-TNF-α drugs (including etanercept [121], infliximab [122], minocyclin [113], thalidomide [123], and celastrol [120]) were shown to reduce NF-κB phosphorylation (active state [48]) in various research models of inflammation. Interestingly, all these drugs reduced AD-like neuropathological features and, when assessed, improved cognitive measures (see references in sections 4.2.2.1–4 above).…”
Section: Evidence That Tnf-α Modulation May Slow or Prevent Alzheimentioning
confidence: 99%
“…Likewise, eliminating microglia prevents neuronal loss and neuroinflammation, and improves memory, without altering levels of Aβ (Spangenberg et al, 2016). Furthermore, administration of minocycline, a tetracyclic antibiotic that inhibits microglial activation, ameliorates AD-like pathology in transgenic mice and downregulates inflammatory markers, partially through inhibition of NFκB, and BACE-1 (Ferretti et al, 2012; Zemke and Majid, 2004). Shifting microglial activation states from the pro-inflammatory M1 to a more anti-inflammatory M2 phenotype has also proven to be effective.…”
Section: Inflammation and Alzheimer’s Diseasementioning
confidence: 99%
“…Non-specific inhibitors of TNFα, such as thalidomide and minocycline, have been tested in AD treatment [7,191193]. …”
Section: Anti-inflammatory Therapy For Ad (2)mentioning
confidence: 99%